Masticator Space Abnormalities Associated with Mandibular Osteoradionecrosis: MR and CT Findings in Five Patients - Chong, June; Hinckley, Lisa K.; Ginsberg, Lawrence E. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Imaging of patients with a clinical diagnosis of mandibular osteoradionecrosis (ORN) is often performed to support that clinical suspicion, evaluate the extent of the disease, or exclude coexistent tumor recurrence. The purpose of our study was to describe the clinical, MR imaging, and CT features of five patients with mandibular ORN associated with prominent soft-tissue abnormality in the adjacent masticator muscles.METHODS: The MR and CT examinations of five patients with mandibular ORN associated with soft-tissue abnormalities in the adjacent masticator muscles were reviewed. All patients had received external beam radiotherapy for primary head and neck malignancies, with a total radiation dose range of 60 Gy to 69 Gy in 30 to 38 fractions.RESULTS: CT revealed the typical osseous findings of cortical disruption, trabecular disorganization, and fragmentation in all five patients. Abnormal diffuse enhancement of the adjacent masseter and pterygoid muscles was noted in all patients. Four patients had prominent mass-like thickening of these muscles adjacent to the osseous abnormality. Of the three patients who underwent MR imaging, all showed homogeneous abnormal T1 hypointensity, T2 hyperintensity, and intense enhancement of the bone marrow in the involved mandible. The masticator muscles adjacent to the osseous abnormality also showed abnormal T2 hyperintensity and intense diffuse enhancement on MR images.CONCLUSION: Mandibular ORN can be associated with prominent soft-tissue thickening and enhancement in the adjacent musculature. These changes can appear mass-like and are not related to tumor recurrence or metastatic disease.